Innovative Activities in The Pharmaceutical Industry in Poland - Marcin OLKIEWICZ (Communications of International Proceedings, 2021)
This publication presents the issues related to the functioning of the pharmaceutical industry. The questions set for this study were the following: How can innovations affect the development of the pharmaceutical industry in Poland, in particular within the scope of manufacturing of medicines? Do the implemented innovations in the pharmaceutical industry determine the quality of life? The analysis revealed interesting dependencies of the development of the pharmaceutical industry, especially within the scope of manufacturing the next-generation pharmaceuticals.
Keywords: Pharmaceutical Industry; Determinants of Development; Quality; Innovation.